THE ROUTLEDGE INTERNATIONAL HANDBOOK OF MULTIDISCIPLINARY PERSPECTIVES ON CHARACTER DEVELOPMENT. Conceptualizing and Defining Character - Matthews, Michael D.; Lerner, Richard M. (Routledge International Handbooks Series, 2024)
These volumes present cutting-edge scholarship about the concept of character across the life span, the developmental and contextual bases of character, and the key organizations of societal sectors, within and across nations, that promote character development in individuals, families, and communities